2018
DOI: 10.1021/acs.cgd.8b01330
|View full text |Cite
|
Sign up to set email alerts
|

A New 1:1 Drug-Drug Cocrystal of Theophylline and Aspirin: Discovery, Characterization, and Construction of Ternary Phase Diagrams

Abstract: A new 1:1 drug-drug cocrystal of theophylline (THP) and aspirin (ASP) was successfully prepared by liquid assisted grinding, evaporative crystallization, and slurry conversion crystallization. The obtained cocrystal was comprehensively characterized by single crystal X-ray diffraction, powder X-ray diffraction, differential scanning calorimetry, thermogravimetric analysis, scanning electron microscopy, and Fourier transform infrared analysis. Ternary phase diagrams were constructed for the obtained cocrystal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 44 publications
2
49
0
2
Order By: Relevance
“…Furthermore, aspirin salts of Li + , Na + , K + , and Rb + are known, and various cocrystals, a few clathrates, and combinations with other drugs have been reported. Among those are aspirin carbamazepine (Vishweshwar et al, 2005), aspirin 5-methoxysulfadiazin (Caira, 1994), aspirin meloxicam (Cheney et al, 2012), aspirin pentoxifylline (Stepanovs et al, 2015), and aspirin theophylline (Darwish et al, 2018). The aspirin meloxicam cocrystallization by NG and LAG using CHCl 3 has been used to model the reactant's approach and molecular mixing during mechanochemical treatment in a ball mill by molecular dynamics calculations (Ferguson et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, aspirin salts of Li + , Na + , K + , and Rb + are known, and various cocrystals, a few clathrates, and combinations with other drugs have been reported. Among those are aspirin carbamazepine (Vishweshwar et al, 2005), aspirin 5-methoxysulfadiazin (Caira, 1994), aspirin meloxicam (Cheney et al, 2012), aspirin pentoxifylline (Stepanovs et al, 2015), and aspirin theophylline (Darwish et al, 2018). The aspirin meloxicam cocrystallization by NG and LAG using CHCl 3 has been used to model the reactant's approach and molecular mixing during mechanochemical treatment in a ball mill by molecular dynamics calculations (Ferguson et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Multidrug combinations are a relatively unexplored and patentable type of materials of increasing interest (Darwish et al, 2018), not only related to crystal engineering studies and the improvement of the physicochemical properties of drugs, but due to monotherapies (one drug to treat one disease) are currently not always considered effective to manage various complex illnesses such as cancer, diabetes, infectious, and cardiovascular diseases (Thipparaboina et al, 2016). Besides, doctors commonly prescribe together various drugs (Sekhon, 2012) and multidrug combinations offer opportunities for exploring synergistic beneficial effects (Darwish et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The phase behavior of the two pure components in the solvent can provide insights into the thermodynamically stable region of each phase and the co-crystallization process. [33][34][35] From our previous work experience, the size and position of the thermodynamically stable region of the cocrystal phase depend on the choice of solvent. 36 Whether it is a pure solvent or a mixture solvent system, the symmetry of the phase diagram depends on the solubility of two pure components in the selected solvent system.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the Carlo patron has reported that aspirin took part in reducing the risk associated with colorectal cancer [35]. Recently, the combinations of aspirin-4,4-bipyridine [36], aspirin-theophylline [37], aspirin-4,4-butane, aspirinpyridinepoly-2-ene [38] were successfully formed stable cocrystals, but none of them have studied the dissolution behavior of aspirin.…”
Section: Introductionmentioning
confidence: 99%